2018
DOI: 10.1038/s41467-018-06589-0
|View full text |Cite
|
Sign up to set email alerts
|

Spin transfer torque driven higher-order propagating spin waves in nano-contact magnetic tunnel junctions

Abstract: Short wavelength exchange-dominated propagating spin waves will enable magnonic devices to operate at higher frequencies and higher data transmission rates. While giant magnetoresistance (GMR)-based magnetic nanocontacts are efficient injectors of propagating spin waves, the generated wavelengths are 2.6 times the nano-contact diameter, and the electrical signal strength remains too weak for applications. Here we demonstrate nano-contact-based spin wave generation in magnetic tunnel junctions and observe large… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…In addition to their applications in memory, STT and SOT play an important role in spin-wave manipulation and the development of spin-wave devices (Madami et al, 2011;Divinskiy et al, 2018;Houshang et al, 2018;Fulara et al, 2019). Madami et al (2011) used STT effect to excite spin waves in a multilayer heterostructure as shown in Figure 6A (CoFe layer as reference/fixed layer and NiFe layer as free layer).…”
Section: Electrical Spin-torque and Magnon-torquementioning
confidence: 99%
“…In addition to their applications in memory, STT and SOT play an important role in spin-wave manipulation and the development of spin-wave devices (Madami et al, 2011;Divinskiy et al, 2018;Houshang et al, 2018;Fulara et al, 2019). Madami et al (2011) used STT effect to excite spin waves in a multilayer heterostructure as shown in Figure 6A (CoFe layer as reference/fixed layer and NiFe layer as free layer).…”
Section: Electrical Spin-torque and Magnon-torquementioning
confidence: 99%
“…Naturally, the mode having the lowest threshold is excited firstly. At large currents, the generation can switch to another regime, e.g., the excitation of higher-order propagating modes [30], second bullet mode [31], multibullet mode [23], mode hopping [32], etc. Here, we are not interested in this high-drivingcurrent dynamics and consider only the lowest excited mode.…”
Section: Excitation Thresholds Of Linearly Localized and Bullet Modesmentioning
confidence: 99%
“…Using magnetic materials as building blocks for these devices allows to reduce their size, taking advantage of their natural resonance in the order of GHz [13,14], which is typically exploited in areas such as magnonics [15][16][17] and spintronics [18][19][20]. In the case of high frequency devices, the use of magnetic materials makes it possible to fabricate micrometer and nanometer devices such as circulators [21,22], phase shifters [23,24], filters [25,26], and frequency sources [27][28][29][30][31][32]. Another characteristic that makes magnetic thin films attractive for high frequency applications is the possibility to control their magnetic properties with electrical signals, providing a path for adjusting dynamically the behavior of magnetic high frequency devices.…”
Section: Introductionmentioning
confidence: 99%